Amino Acid PET Imaging of the Early Metabolic Response During Tumor-Treating Fields (TTFields) Therapy in Recurrent Glioblastoma. (March 2018) - Bosnyák, Edit; Barger, Geoffrey R.; Michelhaugh, Sharon K.; Robinette, Natasha L.; Amit-Yousif, Alit; Mittal, Sandeep; Juhász, Csaba
Abstract : Abstract: Tumor-treating fields (TTFields) therapy is a relatively new treatment approach for malignant gliomas. We evaluated if amino acid PET can detect an objective metabolic response to TTFields therapy in recurrent glioblastomas. PET scanning with alpha[C-11]-methyl-L-tryptophan (AMT) before and 2 to 3 months after the start of TTFields treatment showed an interval decrease of tryptophan uptake in the whole tumor (2 patients) or in a portion of the tumor (1 patient). These data demonstrate that TTFields therapy can induce an early metabolic response in recurrent glioblastoma, and this treatment response can be detected by amino acid PET.